Indole-3-propionic acid promotes Schwann cell proliferation following peripheral nerve injury by activating the PI3K/AKT pathway - Huimei Zhang; Sijia Wang; Qi Zhang; Xinyu Du; Danyang Xu; Jinkun Wen; Mingrui Jin; Jing Liu; Xiaobao Jin; Mengxia Wang; Li Luo; Lixia Li (Neurotherapeutics)
The proliferation of Schwann cells (SCs) is integral for axonal regeneration following peripheral nerve injury, and enhancing their proliferation can accelerate axonal regeneration. Indole-3-propionic acid (IPA), a metabolite of tryptophan synthesized by the intestinal microbiota, has potential in accelerating axonal regeneration in peripheral nerves. Nonetheless, the capacity of IPA to promote SC proliferation remains undetermined. Consequently, this study aimed to investigate the effects of IPA on SC proliferation and the underlying mechanisms. Therefore, we cultured RSC96 ​cells in vitro and used a Cell Counting Kit-8 (CCK8), an EdU Cell Proliferation Detection Kit (EdU), and a Cell Cycle and Apoptosis Assay Kit for the analyses. Additionally, we established a rat sciatic nerve crush injury model in vivo and performed immunofluorescence staining. These findings indicated that IPA enhanced SC proliferation. We further investigated the potential mechanism by which IPA promotes SC proliferation by conducting Western blotting and observed that IPA increased the levels of phosphorylated phosphatidylinositol 3-kinase/phosphatidylinositol 3-kinase (p-PI3K/PI3K) and phosphorylated protein kinase B/protein kinase B (p-AKT/AKT) in RSC96 ​cells, which suggested that IPA may promote the proliferation of RSC96 ​cells by activating the PI3K/AKT pathway. We cultured RSC96 ​cells in vitro, established a sciatic nerve crush model in vivo, and administered a PI3K inhibitor (LY294002) in combination with IPA treatment to validate this hypothesis. Our results revealed a reduction in the proliferation rate of RSC96 ​cells or SCs following the inhibition of p-PI3K/PI3K and p-AKT/AKT expression, as evidenced by the results of the EdU, CCK8 and immunofluorescence staining assays. These findings indicated that IPA may indeed promote SC proliferation through the activation of the PI3K/AKT pathway.